Randomised controlled trial of corticosteroid regimens in endothelial corneal allograft rejection. Issue 12 (1st December 1999) - Hudde, T; Minassian, D C; Larkin, D F P
Abstract : AIM: To determine whether the addition of systemic corticosteroid to local intensive corticosteroid therapy of endothelial corneal allograft rejection improves outcome. METHODS: A prospective randomised treatment trial was carried out at a tertiary referral centre. 36 consecutive corneal graft recipients, presenting with a first episode of endothelial graft rejection, received either (i) one intravenous pulse of methylprednisolone 500 mg in addition to local corticosteroid treatment, or (ii) local treatment only. The regimen of local treatment standardised in all cases for the first 24 hours consisted of one subconjunctival betamethasone 2 mg injection and dexamethasone 0.1% drops in the affected eye every hour for 24 hours. RESULTS: Failure to reverse the graft rejection episode was found in 3/36 (8%) patients. Each of these had been treated with local steroid only. Graft failure from any cause occurred in 9/36 (25%) within 2 years of follow up. No statistically significant difference was found between the two groups with regard to reversal of the graft rejection episode, later recurrence of graft rejection, or graft failure. CONCLUSIONS: In treatment of graft rejection, additional systemic treatment with 500 mg methylprednisolone yields no significant benefit over intensive local corticosteroid alone. Graft survival following treatment of a rejection episode with local corticosteroid treatment alone is good in those patients without other risk factors for graft failure and much higher than reported previously.